Preparation, characterisation, and dielectric properties of polypyrrole-clay composites - ÇAKMAKÇI, EMRAH; ESMER, KADİR; KAHRAMAN, MEMET VEZİR; MADAKBAŞ, SEYFULLAH (SPRINGER INTERNATIONAL PUBLISHING AG, 2013)
In this study, polypyrrole-clay (PPy-clay) composites were prepared by the in situ chemical oxidative polymerisation of pyrrole in the presence of clay. The chemical structures of the composites were characterised by FTIR and XRD analysis. The thermal properties of these novel composites were analysed by TGA and DSC measurements. Glass-transition temperatures and char yields increased with the increase in clay content in the nanocomposites. The interactions between PPy and clay were mainly between polypyrrole and the layers of clay. It was observed that, as the amount of clay in the composites increased, the dielectric permittivity decreased while the dielectric conductivity of the composite materials increased.
Keywords: polypyrrole; clay; thermal properties; dielectric properties; POLYMERIZATION; CONDUCTIVITY; POLYANILINE